The Role of Nursing in the Management of Sepsis in Intensive Care Units: A Comprehensive Review of Leadership Styles and Collaborative Strategies - Samily, Ahmad Khaled Ahmad; ALRUWAILI, GHARAM HUSSAIN MAZKI; Alamrani, Najah; Jerebi, Maryam Ali Abdullah; Alotaibi, Saad Marzouq Nawar; Al-Hafizi, Maryam Saleh; ALOSAIMI, MOHAMMED GHAZI ZAID; Tomihy, Ali Hamad Mohammed; Alblshl, SABAHFAYEZ; Alnjaee, Hanan Ali (Journal of Ecohumanism, 2024)
Background: Strong leadership and good nursing actions are needed in order to treat sepsis in intensive care units (ICUs). A serious illness, sepsis requires fast and coordinated treatment to raise patient outcomes. Methods: This study methodically examines the body of knowledge already in publication on how nurses control sepsis in ICUs. Many databases were searched comprehensively in order to find research on nursing practices, leadership styles, and their effects on patient outcomes and sepsis control. Results: The quality of care in sepsis treatment is evidently much influenced by nurse leadership. Particularly transformative and real leadership styles help to increase team cooperation, communication, and adherence to therapeutic recommendations by means of their influence. Furthermore, proven to lower fatality rates and raise patient satisfaction is the use of standardized procedures for sepsis treatment along with continuous education and training for the nursing team. Conclusion: The leadership and clinical abilities of nurses are essential in the management of sepsis in ICUs. Strong nursing leadership taken in concert with other disciplines improves the quality of treatment given to septic patients. Future studies should concentrate on creating and assessing leadership development initiatives for nurses to maximize sepsis control in critical care environments.